Bacterial composition and community structure of the oropharynx of adults with asthma are associated with environmental factors. (December 2020) - Zhao, Hongcheng; Liu, Jia; Zhu, Jingyuan; Yang, Fan; Wu, Huiying; Ba, Yue; Cui, Liuxin; Chen, Ruiying; Chen, Shuaiyin
Abstract: The development and exacerbation of asthma are mainly attributed to inflammatory reactions caused by allergens. However, less is known about the development of asthma caused by microbial disorders in the oropharynx and induced by environmental factors. Here, the metagenome of the oropharyngeal microbiome of adults with asthma was analysed to identify their association with air pollutants. Oropharyngeal swabs from patients with asthma were collected in two winters (W1 and W2) with different environmental factor exposures. The bacterial composition and community structure of the oropharynx were analysed through high-throughput sequencing. After analysis, the α-diversity and β-diversity exhibited significant differences between the two groups. LEfSe analysis detected 8 significantly different phyla and 11 significantly different genera between the W1 and W2 groups. Multiple linear regression analyses found that the asthma status might contribute to the alteration of microbial composition. Redundancy analysis showed that NO2 was the only environmental factor that significantly affected the microbial community structure of the oropharynx. The different genera associated with NO2 were Rothia, Actinomyces, Fusobacterium and Leptotrichia . The altered taxa related to PM2.5 were Cupriavidus and Acinetobacter . Actinobacillus and Prevotella showed a highly positive correlation with O3 . Moreover, network analysis was carried out to explore the co-occurrence relationships of the main genera, and PICRUSt was conducted to predict bacterial functions. This study showed that environmental factors might cause alteration in the oropharyngeal flora, which might be a potential risk factor of asthma. Highlights: ∙ Under the exposure of different environmental factors, the composition and community structure of the oropharyngeal microbiome in adults with asthma are significantly different. ∙ NO2 may be an important environmental factor that affects the flora of the oropharynx. PM2.5 and O3 can also influence the composition of oropharyngeal microbes to some extent. ∙ Asthma status also contributes to the changes in microbial compositions.